Verbal reports in psychological investigations: a logical and psychological analysis - Praetorius, N.; Duncan, K. D. (Psyke & Logos, 2023)
Since the era of Wundtian introspectionism the status and usefulness of verbal reports from subjects in psychological investigations have been a recurring topic of heated debate and controversy in the international psychological literature. In order to untangle and clearify some of the uncertainties and confusions in this debate, an analysis is attempted of some of the logical and psychological conditions for research involving verbal reports. In the course of this analysis we argue first that any psychological investigation logically presupposes, that communication takes place in a shared language in which both the investigator and the subject know correct statements and descriptions and their correct uses. It is argued, more over, that different areas of psychological research differ distinctively with regard to the opportunities of observation and description - for the investigator and the subject - and, consequently, in the amount of control exercised over events and variables by the investigator and the subject. Examples are given of different psychological conditions and problems encountered in different areas of research and their implications for the development of different research methodes and programmes.